Produktivitas Tanaman padi (Oryza sativa L.) Segreng Terhadap Aplikasi Sludge Biogas di Lahan Sawah Desa Wukirsari, Cangkringan, Sleman - Siswanti, Dwi Umi; Syahidah, Akrima; Sudjino, Sudjino (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2018)
Rice (Oryza sativa L.) is a main crop agriculture in Indonesia. Biogas sludge is the residue of cattle during processing in the biogas that has lost its gas and rich with macro elements – N, P and K as well as micro elements such as Ca, Mg, Fe, Mn, Cu and Zn. Biogas sludge has not been well utilized by the citizens. This study examined the productivity of rice cultivars Segreng to biogas sludge application on field. The objective of this research was to find the best dose of sludge and to study the productivity of rice cultivars Segreng after sludge application on crop field. Research was conducted in 100 m2 of field. The biogas sludge concentration used in this research was 5 variations; (1) 0 ml, (2) 1000 ml, (3) 2000 ml, (4) 3000 ml, dan (5) 4000 ml. The planting system used is TAJARWO. The productivity parameter measured were Nitrate Reductase Activity (NRA), dry weight, number of grain per plant and grain weight. Environment parameters were temperature, pH, humidity and light intensity. The data was analyzed with ANOVA and followed by DMRT at significant level of 5%. The results revealed that the highest rice productivity was seen in treatment 2000 ml sludge/100m2 with 31 gr of dry weight, 483 number of grains per plant and 30.000 kg/100m2 of grain weight. The best sludge dose present on 2000 ml/100m2.